Effects of different natural exogenous additives on the physicochemical and flavor properties of crispy fried spareribs - Fanyi Gong; Qingyang Meng; Bowen Liao; Buzhou Xu; Yong Tang; Chang Su; Dong Zhang (Food Science of Animal Products)
This study aimed to investigate the effects of different exogenous additives on the physicochemical properties and volatile flavor substances of crispy fried spareribs. Results showed that the addition of rattan pepper, Houttuynia cordata, Litsea, and plum had no significant effect (P > 0.05) on the texture properties of crispy fried spareribs. These ingredients had a certain effect on the thiobarbituric acid reactive substances value of crispy fried spareribs, but the difference was not significant (P > 0.05). Moreover, they could improve the sensory scores of crispy fried spareribs to a certain extent. A total of 91 volatile flavor substances were identified from 5 groups of crispy fried spareribs. Adding exogenous additives increased the types and contents of volatile flavor substances in crispy fried spareribs and increased the contents of key volatile flavor substances such as 1-octen-3-ol, linalool, 1-hexanol, and 1-dodecen-3-ol. Combined with sensory scores and physicochemical indexes, these findings showed that adding rattan pepper, H. cordata, Litsea, and plum could improve the taste and quality of crispy fried spareribs, thus having good application prospects.